21st century pharmacovigilance: efforts, roles, and responsibilities. Issue 11 (November 2016) - Pitts, Peter J; Louet, Hervé Le; Moride, Yola; Conti, Rena M
Summary: In an era when the number of expedited and conditional review pathways for newly available brand-name drugs and biosimilar medicines to treat serious and life-threatening diseases is increasing, defining pharmacovigilance has never been more crucial. 21st century pharmacovigilance is not merely about uncovering, reporting, and addressing adverse events associated with already approved and marketed agents, but can be described as the systematic monitoring of the process of pre-market review and post-market surveillance, which includes the use of medicines in everyday practice. Pharmacovigilance identifies previously unrecognised adverse events or changes in the patterns of these effects, the quality and adequacy of drug supply, and should ensure effective communication with the public, health-care professionals, and patients about the optimum safety and effective use of medicines. In this paper, the first in a Series of three about drug safety in oncology, we discuss evolving challenges in the purview, roles, and responsibilities of the US Food and Drug Administration and the European Medicines Agency with respect to pharmacovigilance efforts, with a special emphasis on oncology treatment.